Organellar genome divergence and environmental stress induce transcriptional cytonuclear responses in wheat alloplasmic hybrids - Yue Zhao; Keren Zhang; Guo Li; Yuming Wang; Xiaoyang Ding; Shuo Wang; Xi Pang; Xueru Zhao; Yue Yu; Jiaqi Liu; Tingting Yu; Guixian Bao; et al. (Proceedings of the National Academy of Sciences, 2025)
The union of two or more different nuclear genomes with maternally inherited organellar genomes may lead to cytonuclear incompatibilities in plant allopolyploids. These incompatibilities may be reconciled by coevolutionary responses at the genomic and transcriptional levels. To date, the relationship between extent of divergence among parental organellar genomes and cytonuclear coevolutionary responses remains largely unexplored. Here, we studied transcriptional cytonuclear expression in synthetic alloplasmic allohexaploid wheat lines having the same nuclear subgenomic composition (the nuclear genome of Chinese Spring) but with varying cytoplasmic organelles (plasmon donors from B- and D- lineage Triticum/Aegilops species). A positive association between the extent of plastid organellar divergence from naturally occurring organelles in euplasmic Chinese Spring and transcriptional cytonuclear responses was observed. This response was enhanced under stress (highlight) treatment and was determined to be related to differential subgenomic methylation levels. These data comprise a transcriptional dimension of cytonuclear responses to polyploidy and point to a potentially responsible epigenomic regulatory mechanism.